2008
DOI: 10.1016/j.ehb.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Geography of underweight and overweight among women in India: A multilevel analysis of 3204 neighborhoods in 26 states

Abstract: We investigated the geographic distribution and the relationship with neighborhood wealth of underweight and overweight in India. Using multilevel modeling techniques, we calculated statespecific smoothed shrunken state residuals of overweight and underweight, neighborhood and state variation of nutritional status, and the relationships between neighborhood wealth and nutritional status of 76,681 women living in 3204 neighborhoods in 26 Indian states. We found a substantial variation in overweight and underwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 48 publications
7
34
0
Order By: Relevance
“…Low quality, high calorie foods are increasingly easy to obtain for those who have even the smallest amount of disposable income. This observed relationship between gender and skinfold thickness is consistent with evidence from other developing countries stating that women experience the nutrition transition, and overnutrition differently than their male counterparts (Ackerson et al, 2008;Mendez et al, 2003;Steyn et al, 1998). These results suggest that the variability observed in body mass index Z-score values and skinfold thickness Z-score values for individuals in different age cohorts cannot be fully explained by variability in socioeconomic status.…”
Section: Economic Status and Body Compositionsupporting
confidence: 88%
“…Low quality, high calorie foods are increasingly easy to obtain for those who have even the smallest amount of disposable income. This observed relationship between gender and skinfold thickness is consistent with evidence from other developing countries stating that women experience the nutrition transition, and overnutrition differently than their male counterparts (Ackerson et al, 2008;Mendez et al, 2003;Steyn et al, 1998). These results suggest that the variability observed in body mass index Z-score values and skinfold thickness Z-score values for individuals in different age cohorts cannot be fully explained by variability in socioeconomic status.…”
Section: Economic Status and Body Compositionsupporting
confidence: 88%
“…Like Hb, there are clear education gradients in underweight and overweight, particularly for women. This is consistent with previous evidence on younger Indians (Subramanian et al, 2009), as well as results on large state differences (Ackerson et al, 2008). We find that about one third of Indians have a CRP level considered to be high risk (>3 mg/L), which is comparable to results from the English Longitudinal Study on Ageing (Hamer and Molloy, 2009).…”
Section: Resultssupporting
confidence: 92%
“…Third, given the growing prevalence of obesity in developing countries and its association with NCDs (Ackerson et al, 2008;Kearney et al, 2005;Popkin et al, 2001;Prentice, 2006), we also examine the risk factors for being underweight and overweight. We hypothesize similar education gradients in BMI to the gradients we observe for hemoglobin (Subramanian et al, 2009).…”
mentioning
confidence: 99%
“…In the Philippines, Colchero and Bishai (2008) found that the average BMI among women living in neighborhoods with telephones, electricity, mail delivery and newspapers (a proxy of socioeconomic status) was higher than the values observed among women living in places with up to two of these public amenities. In India, data from 3 204 neighborhoods in 26 states showed a positive association between neighborhood socioeconomic status and BMI (Ackerson et al 2008). Finally, analyzing data from a lowincome country-Burkina Faso, Ouédraogo et al (2008) reported a positive association between obesity and living in structured and high building-density areas.…”
Section: Discussionmentioning
confidence: 92%